Prosumer-Led Network Effects of Distributed Energy Resources - Eggleston, James David (Curtin University, 2022)
This thesis attributes the value captured by prosumers from Distributed Energy Resources (DER) to network effects. By answering this in the positive, I show how each additional DER prosumer brings incrementally greater value, pointing the way to enshrining the role of the prosumer in electric-power networks. The novel contribution of this thesis lays in the new perspectives and learnings drawn from the network effects developed by the information-communication revolution and applied to electric-power networks.